Robust Frame-Based Beamforming Scheme to Enhance Secure Multigroup Multicast Transmission for Multibeam Satellite Systems - Zhao, Bai; Lin, Min; Li, Fei; Cheng, Ming; Al-Dhahir, Naofal (IEEE transactions on vehicular technology, 2024)
In this article, we propose a robust frame-based beamforming (BF) scheme to enhance the physical layer security for multigroup multicast transmission in a multibeam satellite system. By assuming that only the imperfect channel state information of each user is known, we formulate a constrained optimization problem to maximize the minimal transmission-outage rate with fairness, subject to outage probability (OP) constraints of all satellite terminals (STs), the intercept probability (IP) constraint of an eavesdropper (Eve), and the per-feed power budget. To cope with this complicated optimization problem, we first propose to adopt the Bernstein Inequalities, norm compatibility and S -procedure to convert the OP and IP constraints into deterministic forms. Then, we propose a robust frame-based secure multigroup multicast BF scheme to solve it efficiently. Finally, our simulation results demonstrate the superiority and robustness of the proposed robust BF scheme, and confirm that our proposed scheme can significantly improve the security and reliability for multibeam satellite systems.